Dynamic analysis of an elastic ring squeeze film damper supported rotor using a semi-analytic method. Issue 1 (1st January 2020) - Han, Zhifei; Ma, Zhisai; Zhang, Wei; Han, Bingbing; Ding, Qian
Abstract : To speed up the calculation of dynamic analysis for elastic ring squeeze film dampers (ERSFDs) and investigate the dynamic characteristics of ERSFD-rotor systems, a semi-analytic method (SAM) is proposed for analyzing oil film pressure and force. This method is subsequently verified by comparison with numerical simulation and experimental results. Based on this SAM, an improved dynamic model of an ERSFD-supported rotor is developed by coupling the kinetic equations of the rotor with the determination of elastic deformation. Using this method, the oil coefficients and vibration behaviors of the rotor such as the amplitude–frequency relation and the influence of sudden excitation are investigated. The results reveal that the equivalent oil coefficients and damping ratio of the system can be increased significantly by the adoption of ERSFDs. Therefore, the nonlinear bi-stable response occasionally occurring in traditional squeeze film damper (SFD) supported rotors is effectively suppressed and the transient vibration process caused by sudden unbalanced excitation action is significantly shortened. The SAM enables one to reduce the computation time of the previous method by more than 90%. Such a reduction greatly improves the computational efficiency.